FEEDING THE MIND: A SYSTEMATIC REVIEW OF HOW NUTRITIONAL CHOICES AFFECT THE MENTAL WELL-BEING OF THE ELDERLY - Maulana, Irsyan Baginda; Sincihu, Yudhiakuari (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Introduction: Mental well-being is a significant concern for the aging population. With the increasing prevalence of the elderly, identifying effective strategies to improve their mental well-being is crucial. Objectives: This systematic review aims to assess the impact of nutritional choices on the mental well-being of older adults, synthesizing evidence on how diet influences mental health outcomes in this demographic. Materials and Methods: Following PRISMA guidelines, peer-reviewed studies from 2020 to 2023 were sourced from PubMed. The review focused on randomized controlled trials (RCTs) involving elderly participants (65 years and older) and examined the effects of specific nutritional choices on mental well-being outcomes. Results: From an initial pool of 394 studies, 5 were included in the qualitative synthesis. Key findings highlight the positive impact of diets rich in omega-3, omega-6, polyphenols, vitamin E, carotenoids, and probiotics on cognitive function, stress reduction, and overall mental well-being. Conclusion: This review underscores the significant role of nutrition in enhancing mental health among older adults. Effective dietary interventions can play a critical role in mitigating mental health disorders in the elderly, highlighting the need for comprehensive dietary guidelines tailored to this vulnerable population.